Hubungan Penggunaan Dopamin Agonis dengan Kualitas Tidur pada Pasien Parkinson - Silalahi, Elsa D.; Warouw, Finny; Mahama, Corry N. (Medical Scope Journal, 2026)
Abstract:  Parkinson’s disease is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, including sleep disturbances that reduce quality of life. Dopamine agonists such as pramipexole and ropinirole not only improve motor symptoms but may also affect sleep quality in Parkinson’s disease patients. This study aimed to evaluate the correlation between the use of dopamine agonist and sleep quality in Parkinson’s disease patients. This was an analytical and observational study using a cross-sectional design, involving 34 outpatient Parkinson’s disease patients at the CVBC Neurology Clinic of Prof. Dr. R. D. Kandou Hospital in September 2025. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and data were analyzed with the chi-square test. The results showed that of the 34 patients, 18 used dopamine agonists and 16 did not. Good sleep quality was observed in 72.2% of dopamine agonist users compared with 25% of non-users. There were significant correlations between dopamine agonist use and sleep quality (p=0.006), and between age and sleep quality (p=0.010). Meanwhile, sex, comorbidities, and disease duration did not show significant correlations. In conclusion, there is a significant correlation between the use of dopamine agonist and sleep quality in Parkinson’s disease patients. Dopamine agonist users tend to have better sleep quality than those who do not use them. Keywords: Parkinson’s disease; dopamine agonists; sleep quality; non-motor symptoms    Abstrak: Penyakit Parkinson (PP) merupakan gangguan neurodegeneratif progresif dengan gejala motorik dan nonmotorik, termasuk gangguan tidur yang dapat menurunkan kualitas hidup pasien. Dopamin agonis seperti pramipeksol dan ropinirol tidak hanya memperbaiki gejala motorik tetapi juga diduga berpengaruh terhadap kualitas tidur pasien PP. Penelitian ini bertujuan untuk mengetahui hubungan antara penggunaan dopamin agonis dengan kualitas tidur pada pasien PP. Jenis penelitian ialah observasional analitik dengan desain potong lintang yang melibatkan 34 pasien PP rawat jalan di Poliklinik Saraf CVBC RSUP Prof. Dr. R. D. Kandou Manado pada bulan September 2025. Teknik pengambilan sampel menggunakan consecutive sampling dengan menggunakan kuesioner Pittsburgh Sleep Quality Index (PSQI), data rekam medik, dan dianalisis menggunakan uji chi-square. Hasil penelitian mendapatkan dari 34 pasien, 18 pasien menggunakan dopamin agonis dan 16 pasien tidak. Sebanyak 72,2% pasien pengguna dopamin agonis memiliki kualitas tidur baik, sedangkan pada kelompok non-pengguna hanya 25%. Terdapat hubungan bermakna antara penggunaan dopamin agonis dan kualitas tidur (p=0,006); dan antara variabel usia dan kualitas tidur (p=0,010). Jenis kelamin, komorbiditas, dan lama menderita tidak menunjukkan hubungan bermakna. Simpulan penelitian ialah terdapat hubungan bermakna antara penggunaan dopamin agonis dengan kualitas tidur pada pasien penyakit Parkinson. Pasien penyakit Parkinson yang menggunakan dopamin agonis memiliki kualitas tidur yang lebih baik dibandingkan pasien yang tidak menggunakan. Kata kunci:  penyakit Parkinson; dopamin agonis; kualitas tidur; simtom nonmotorik